The Effect of Silver Nanoparticles Stabilized with Tannic Acid for Nano-Priming on Zea mays L. Seeds Germination - Handayani, Windri; Tanadi, Richard Owen; Umar, Aminah (Universitas Sebelas Maret, 2025)
Silver nanoparticles (AgNPs) have various benefits for application in the agricultural sector, such as nano-seed priming to enhance seedling growth and development. In this research, the effectiveness of AgNPs sizes and concentration to enhance Zea mays seeds germination has been investigated. The AgNPs were synthesized using various concentrations of tannic acid (0.025, 0.25, and 5 mM) to produce AgNPs with different sizes to know their optimum size and concentration. The synthesized AgNPs were characterized using a UV-Vis spectrophotometer to determine the absorption spectrum of AgNPs within 400 to 500 nm. Besides that, a transmission electron microscope (TEM) was used to determine the size and shape of the AgNPs, and an atomic absorption spectrophotometer was used to determine the concentration. The results show AgNPs with sizes of 13.39±2.40, 27.25±4.09, and 46.7±10.75 nm, respectively. Subsequently, AgNPs with concentrations of 8, 16, and 24 mg l-1 were exposed to Z. mays seeds for 24 hours, then germinated for 14 days. The results revealed that AgNPs with a size of 27 nm and a concentration of 24 mg l-1 showed the highest germination rate and growth despite the control and other treatments. This indicates that the AgNPs with those properties have the potential as a seed nano-priming agent.